Storage of tomato (Solanum lycopersicum) covered with sapote gum (Capparis scabrida) (Agroindustrial Science, 2022)
The coating of tomato with sapote gum (0.0%, 0.5%, 1%, 2.5% (w/v)) was evaluated during storage in the environment (20 °C; 85 % RH) and refrigeration (15 °C; 90% RH). Treatments with coverage to the environment presented less weight loss than the control (0.0%); in refrigeration, in treatments with 0.5% and control, this loss was lower. The rate of respiration to the environment and refrigeration showed similar trends. There was a non-significant increase in ambient soluble solids; in refrigeration, the control presented a slight decrease and the treatments with coverage a slight increase. The pH, in all treatments, was slightly increased. There was a slight decrease in acidity in all treatments. Firmness decreased by 46%-55% in the environment and by 65%-69% in refrigeration; there were no significant differences with respect to the witness. The color parameters (L*, h° and C*) decreased significantly in the first week; afterward, the decrease was slight. The mold and yeast count were below the maximum limits. Sensorily, acceptance was similar in all treatments. In conclusion, the physicochemical and microbiological characteristics and acceptability of the rubber-coated tomato did not show significant differences with respect to the control.
Keywords: tomato; zapote; gum; storage